"That's Not His Regular Formula": A Case of Organophosphate Poisoning in an Infant. Issue 4 (April 2021) - Dodson, Jeannette; Feng, Sing-Yi; Rodriguez, David
Abstract : Introduction: Organophosphates (OPs) are the basis of many insecticides and herbicides and are also used as nerve agents. Approximately 1 million unintentional and 2 million suicidal poisonings as well as more than 300, 000 fatalities that are reportedly due to OPs are reported each year worldwide. The mortality rate from OP toxicity is reported as approximately 20%. We present a rare pediatric exposure to OPs. Case: This is an unintentional OP poisoning in an infant who presented to a pediatric emergency department with obtundation, respiratory distress, and copious secretions. The infant was intubated, treated with atropine and pralidoxime after resuscitation, and eventually recovered with no neurologic sequelae. Discussion: Symptoms from OP toxicity are secondary to effects on muscarinic and nicotinic cholinergic receptors in the autonomic and central nervous systems. Symptoms include diaphoresis, diarrhea, urination, miosis, bradycardia, bronchospasm, bronchorrhea, emesis, lethargy, lacrimation, and salivation. Treatment starts with titrated doses of atropine and oximes (eg, pralidoxime) after resuscitation and decontamination. Severity of toxicity and recovery can be monitored via plasma and whole blood acetylcholinesterase levels, respectively. Once aging has occurred, oximes will not be able to reverse acetylcholinesterase inhibition. Despite early treatment, rare cases may result in delayed neurologic complications associated with sensory and motor axonal degeneration of the peripheral nerves and spinal cord known as OP-induced delayed neuropathy. Conclusions: This case highlights the importance of safety education for families. It also demonstrates how to recognize and treat OP toxicity in an infant. It emphasizes starting treatment early to avoid complications secondary to aging.